The Intersectionality of Gender and Wealth in Adolescent Health and Behavioral Outcomes in Brazil: The 1993 Pelotas Birth Cohort - Buffarini, Romina (J Adolesc Health, 2020)
PURPOSE: Brazilian society is characterized by deep socioeconomic inequalities. Using data from a population-based birth cohort, we explored how the intersectionality of family income and gender may affect adolescent health and behavioral outcomes. METHODS: Children born in 1993 in the Brazilian city of Pelotas have been followed up prospectively at the age of 15 years when the follow-up rate was 85.7% of the original cohort. Participants answered standardized questionnaires, and anthropometric measures were obtained. Outcomes in five domains were studied: overweight (body mass index above +1 SD of the World Health Organization standard for age and sex), cigarette smoking (in the previous month), violence (fight in which someone was injured, in the past year), self-reported unhappiness (based on a face scale), and psychological symptoms (Strengths and Difficulties Questionnaire). Monthly family income was recoded in quintiles. RESULTS: Results were available for more than 4,101–4,334 adolescents, depending on the outcome. Overweight was more common among boys than girls (29.7% and 25.6%; p = .004) and was directly related to family income among boys (p < .001), but not among girls (p = .681). Smoking was less common among boys than girls (12.3% and 21.0%, p < .001) and showed strong inverse association with income among girls (p < .001), but not among boys (p = .099). Reported violence was twice as common among boys than girls (16.4% vs. 8.0%; p < .001); an inverse association with income was present among girls (p < .001), but not for boys (p = .925). Boys and girls were similarly likely to report being unhappy (18.4% and 20.1%; p = .176), with an inverse association with family income in girls. Psychological symptoms were slightly less common among boys than girls (25.3% and 28.3%; p = .014), with strong inverse associations with income in both sexes (p < .001). Adolescent girls from poor families were the group with the highest prevalence for three of the five outcomes: smoking, unhappiness, and psychological problems. CONCLUSIONS: Gender norms influence adolescent health and behavioral outcomes, but the direction and strength of the associations are modified by socioeconomic position. Preventive strategies must take into account the intersectionality of gender and wealth.